DECLINE OR DEVELOPMENT OF THE ATM SERVICES AND THEIR SOCIAL ACCEPTABILITY - Jacek Binda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper is focused on the still growing market of ATM devices and presents the growth of this market against the background of rapidly developing risks associated with electronic banking services. The paper also lists changes related to the progress in this particular channel of contact and presents alternative forms of communication between a bank and its clients. The paper also highlights the efforts undertaken by the banking sector towards reducing the presence of cash in the financial turnover and lowering the costs of cash transactions due to development of high-tech ATM devices. A growing number of available services, crucial for the ATM functionality and the level of ATMs social acceptability, however multiply the number of risks accompanying this process. Understanding various attack vectors and crimes is crucial to win the race with digital criminals and reduce the number of thefts. The paper quotes data obtained from the Polish National Bank, the Polish Banks Association and EAST.